Acute and Chronic Effects of Citalopram on Cerebral Glucose Metabolism in Geriatric Depression - Smith, Gwenn S.; Kramer, Elisse; Hermann, Carol R.; Goldberg, Sara; Ma, Yilong; Dhawan, Vijay; Barnes, Anna; Chaly, Thomas; Belakhleff, Abdel; Laghrissi-Thode, Fouzia; Greenwald, Blaine; Eidelberg, David; et al. (The American journal of geriatric psychiatry, 2002)
In vivo studies of serotonin function have been limited by the lack of safe and selective pharmacologic agents and availability of suitable radiotracers. In the present study, the authors evaluated the cerebral metabolic effects of acute and continued administration of the selective serotonin reuptake inhibitor citalopram in patients with geriatric depression as a potential marker of serotonin dysfunction. Six patients with geriatric depression and five comparison subjects underwent two resting positron emission tomography (PET) studies, performed after administration of a placebo infusion (Day 1) and a citalopram infusion (40 mg, Day 2). The patients were re-scanned after 8 weeks of treatment with the oral medication. The elderly comparison subjects demonstrated greater right-hemisphere cortical decreases than the patients. The depressed patients demonstrated greater left-hemisphere cortical decreases than comparison subjects. The depressed patients demonstrated greater increases in the right putamen and left occipital cortex. After 8 weeks of citalopram treatment, regional decreases and increases in metabolism were observed These findings suggest regional deficits and also compensatory responses in the acute metabolic response to citalopram in the patients. These preliminary results suggest that the cerebral metabolic response to citalopram may be a useful marker of the pathophysiology of serotonin function in geriatric depression.